PENGARUH MEDIA EDUKASI VIDEO ANIMASI TERHADAP PENGETAHUAN GIZI SEIMBANG PADA ANAK SEKOLAH DASAR (Jurnal Kesehatan Siliwangi, 2023)
Background: Indonesia still faces serious nutritional problems regarding the quality of its human resources (HR). In school children, the incidence of overweight and obesity is a serious problem because it will continue into adulthood and is a risk factor for various non-communicable diseases. Purpose: to determine the effect of animated video media on knowledge of balanced nutrition in elementary school children. Method: Quasy Experiment One Group Pretest Posttest. The sample of this study used a total sampling of 33 students. Results: Univariate analysis with a mean pretest of 75.15 and posttest of 88.79, an increase of 18.15%. Bivariate analysis with Wilcoxon obtained a P-Value of 0.001. The results of this study prove that animated video educational media can increase respondents' knowledge about balanced nutrition because it is proven to attract attention, increase retention, and can explain a material in a real way by visualizing the material described can be described. So that the process of Awareness, Interest, Desire, and Action can run better. Conclusion: the influence of animated video educational media on knowledge of balanced nutrition in elementary school children.